Parole and Probation Officers' Perceptions of Management Effectiveness in Baltimore County, Maryland - Johnson, Valencia Tamir (2015)
Management practices in the rehabilitation and criminal justice system are primarily concerned with how employees sense, collect, organize, and process information regarding the criminal offender. The purpose of this quantitative study was to measure parole and probation officers' perceptions regarding management support and effectiveness in the workplace, with particular emphasis on communication, collaboration, and conflict resolution. Herzberg's 2-factor theory of motivation served as the theoretical framework for the study, supporting the concept of participatory management as a central factor in job satisfaction. A researcher-designed, Likert-type questionnaire was administered to a randomly selected sample of 31 parole and probation officers in Baltimore County. The sample size was determined using a power analysis for the 2-sample t test. The power analysis was completed with alpha levels of .05, and a .80 level of statistical power. Participants had been employed for at least a year as parole and probation officers who supervised African American criminal offenders. Results from the questionnaires were analyzed using t tests, frequency distribution analysis, and comparison of means analysis, with mixed findings. The majority of participants felt that managers provide a positive overall work environment and effectively communicate with parole and probation officers. At the same time, the majority of respondents also believed that managers do not collaborate with employees and do not resolve conflicts with employees in a timely manner. Possible reasons for these contradictory perceptions are discussed. The study contributes to positive social change by providing leaders with improved methods for measuring parole and probation officers' perceptions regarding managerial support for and effectiveness in the rehabilitation of reentry offenders